РЕЗУЛЬТАТЫ ИССЛЕДОВАНИЯ ПО МЕТОДУ СОЦИОМЕТРИИ И РИСУНОЧНЫМ ТЕСТАМ - Клычева, З.П. (SCIENCE and SOCIETY, 2025)
This article provides well-known sociometric methods and drawing tests for studying interpersonal relationships. The methods allow the teacher to study very complex relationships in the classroom, identify and determine the place of each student in the system of interpersonal relationships.